Universal child allowances in 14 middle income countries: Options for policy and poverty reduction - Martin Evans; Alejandra Hidalgo; Mei Wang (Luxembourg Income Study (LIS), 2018)
This paper uses data from 14 Middle Income Countries in the Luxembourg Income Study database to examine the position of children in the income distributions, and to calculate child poverty prevalence, to assess how far children receive transfers from state social protection systems compared to other agegroups. The results show that children are disproportionately concentrated in the lower quintiles and have higher child poverty prevalence than for adults, but receive lower social protection transfers on a per-capita basis across all 14 countries. The analysis then moves to consider how the introduction of a simulated "universal child allowance" based on a new allocation of 1 percent of GDP across all 14 countries could be designed to achieve both universal and targeted, anti-poverty, outcomes. Different versions of simple static and purely arithmetic micro-simulations are used to examine how a universal approach that allocates transfers to all children aged 0-17 can be adapted to optimise poverty reduction - both for child and general poverty. These simulations examine changes to poverty reduction moving from household to individual level allocation, weighting higher levels of transfers to younger children and of "taxing back" universal transfers to those with incomes in the highest three quintiles. The findings show that individual allocation and "taxing back" from higher income quintiles have the largest poverty reduction effect across all 14 countries, while weighting transfers to younger children has different poverty reduction effects between countries - depending on age composition and co-residence. The results are discussed in the light of debates on "targeting" verses "universal" approaches to social protection.
Keywords: D31; H53; I32; I38; 330; poverty; social policy; children